Metals in Mediterranean aquatic species. Issue 1 (15th May 2015) - Iamiceli, AnnaLaura; Ubaldi, Alessandro; Lucchetti, Dario; Brambilla, Gianfranco; Abate, Vittorio; De Felip, Elena; De Filippis, Stefania P.; Dellatte, Elena; De Luca, Silvia; Ferri, Fabiola; Fochi, Igor; Fulgenzi, AnnaRita; et al.
Highlights: Study on metals in Mediterranean fish and fishery products. Data collected for several contaminants in wild and farmed species of commercial interest. Samples compliance with EU regulatory limits. Identification of Mediterranean Sea areas showing background concentrations. An interpretation of the chemical pollution issue of Marine Framework Strategy Directive. Abstract: Metals such as arsenic (As), cadmium (Cd), copper (Cu), chromium (Cr), nickel (Ni), lead (Pb), vanadium (V), have been determined in species of Mediterranean marine organisms collected from areas supposed to be at background contamination levels. The Inductively Coupled Plasma Mass Spectrometry (ICP-MS) approach was adopted for the determination of all the metals. Arsenic, Cd and Pb determined in the 42 samples, do not exceed the pertinent maximum level except a sample of hake. In wild fish, the concentration range for Cr, Ni, V and Cu was, respectively: 0.07–0.09, 87.6–124, 0.022–0.075 and 0.79–1.74 μg/g fresh weight (fw). The farmed fish samples show concentration levels below the wild fish ones, except for Cr which range at the same levels. Cadmium and Pb show a high sample number under the quantification limit. The elements do not bio-magnify among the species considered and appear to show low variations in relation to organisms' position in the food chain and at sampling sites.